Pengaruh Leverage dan Likuiditas Terhadap Kebijakan Dividen Pada Perusahaan Manufaktur di Bursa Efek Indonesia Tahun 2020 – 2023 - Qatrunnada Salsabila; Oryza Sativa; Muhammad Nur Faizin Ramadhan; Isti Pujihastuti (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
This research is important to provide valuable insight for companies in determining the optimal dividend policy and attracting investor interest. Hopefully, this research can make a significant empirical and theoretical contribution regarding the effect of leverage and liquidity on dividend policy in manufacturing companies on the IDX for the 2020-2023 period and can be a reference for companies in making decisions. This study uses some independent variables, namely Leverage and Liquidity. The dependent variable is the Dividend Policy which uses a purposive sampling method on one hundred samples of manufacturing companies on the IDX. In this case, H1 is accepted, leverage has a significant effect on dividend policy with a path coefficient (-0.055) and p-value (0.000 < 0.005). Then H2 is accepted, liquidity has a significant impact on dividend policy with path coefficient (0.109) and p-value (0.050 < 0.005). In this study, the data collected by researchers is quite limited, so future researchers are expected to develop data updates from previous studies where future researchers can find other variables that can affect dividend policy.